2022
DOI: 10.1155/2022/7150304
|View full text |Cite
|
Sign up to set email alerts
|

Correlation Analysis of Pathological Features and Axillary Lymph Node Metastasis in Patients with Invasive Breast Cancer

Abstract: Objective. To investigate the risk factors of axillary lymph node metastasis in patients with invasive breast cancer. Methods. This study retrospectively included 122 cases of invasive breast cancer patients admitted to the First Medical Center of PLA General Hospital from January 2019 to September 2020. According to postoperative pathological results, axillary lymph node metastasis was divided into axillary lymph node metastasis (ALNM) group ( n … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 38 publications
0
7
0
Order By: Relevance
“…The research on the factors related to the prognosis of various diseases is the current research focus (36)(37)(38)(39). It is suggested that Dabuyin pill can inhibit the development of secondary sexual characteristics, reduce the volume of the uterus and ovaries, slow down the speed of bone maturation, and has no adverse reactions.…”
Section: Discussionmentioning
confidence: 99%
“…The research on the factors related to the prognosis of various diseases is the current research focus (36)(37)(38)(39). It is suggested that Dabuyin pill can inhibit the development of secondary sexual characteristics, reduce the volume of the uterus and ovaries, slow down the speed of bone maturation, and has no adverse reactions.…”
Section: Discussionmentioning
confidence: 99%
“…The research on the prognosis and related biological indicators of different diseases is the focus of current research (26)(27)(28)(29)(30). The parameters of breast dynamic enhancement MRI in young breast cancer patients are specific, which is manifested by an increased proportion of patients with non-mass enhancement, a decrease in the ADC, and is related to the clinical features and prognosis of patients.…”
Section: Discussionmentioning
confidence: 99%
“…Prognosis and related indicators of different diseases are the focus of current research (26)(27)(28)(29). Our model could accurately identify high risk of death within 5 years of surgery in non-small cell lung cancer patients.…”
Section: Discussionmentioning
confidence: 99%